The Role of ICT in Management of Meeting Minutes at Politeknik Enjinering Indorama - Muhammad Nugraha; Heti Mulyani; Musawarman Musawarman (Jurnal Informatika: Jurnal Pengembangan IT, 2021)
Meetings are routine activities at Politeknik Engineering Indorama such as management meetings, senate meetings, committee meetings, and some other meetings. One of the important things about a meeting is minutes of meeting because minutes of a meeting are written evidence that the meeting was held and the result can be used as a reference in making policies at Politeknik Engineering Indorama. The method of writing and documenting of minutes meeting will not be effective and efficient if we still use the manual method, because in the future it will be difficult to find the result and documentation of the meeting if needed. Because of this, in managing minutes meeting and documenting it is necessary to use an information system in order for the process of documenting and searching more effectively and efficiently. Hence, in this research, we will design and build a minute meeting management system to simplify the process of documenting and searching.